Prioritized heterogeneous traffic-oriented congestion control protocol for WSNs - Monowar, Muhammad Mostafa; Rahman, Md. Obaidur; Pathan, Al-Sakib Khan; Choong, Seon Hong (Zarqa University, Jordan, 2012)
Due to the availability of multiple sensing units on a single radio board of the modern sensor motes, some sensor networks need to handle heterogeneous traffic within the same application. This diverse traffic could have different priorities in terms of transmission rate, required bandwidth, packet loss, etc. Because of the multi-hop transmission characteristic of this prioritized heterogeneous traffic, occurrence of congestion is very common and unless handled effectively, it could thwart the application objectives. To address this challenge, in this paper we propose a Prioritized Heterogeneous Traffic-oriented Congestion Control Protocol (PHTCCP) which performs hop-by-hop rate adjustment controlling the congestion and ensures efficient rate for the prioritized diverse traffic. This protocol also could be applied for healthcare infrastructure. We exploit cross layer approach to perform the congestion control. Our protocol uses intra-queue and inter-queue priorities along with weighted fair queuing for ensuring feasible transmission rates of heterogeneous data. It also guarantees efficient link utilization by using dynamic transmission rate adjustment. We present detailed analysis and simulation results with the description of our protocol to demonstrate its effectiveness in handling prioritized heterogeneous traffic in Wireless Sensor Networks (WSNs).